The biomechanics of freestyle and butterfly turn technique in elite swimmers - Nicol, E.; Ball, K.; Tor, E. (Sports Biomechanics, 2021)
The swimming turn significantly contributes to overall race performance. Whilst the importance of the turn is well established within the literature, the biomechanical parameters that are most important to turn performance remain unclear. The aim of this study was to identify the key biomechanical parameters that influence freestyle and butterfly turn time within an elite population. An elite population was defined to include athletes who had represented Australia at a minimum of one international competition. Retrospective data from 39 male freestyle turns, 41 female freestyle turns, 21 male butterfly turns and 23 female butterfly turns were analysed. Regression analysis was used to identify the biomechanical parameters (e.g., peak power per kg, total time in underwater work) that were important to turn performance. Analysis revealed that no individual parameter strongly predicted turn performance for any of the investigated subsets. Results of the present study suggest that a holistic approach should be taken to improve turn performance. This would involve making technique changes to a number of biomechanical parameters rather than focussing on a single parameter. Developing training programmes in this way will increase the effectiveness of prescribed interventions and assist in maximising improvement made to turn performance.